OPTIMIST AND PESSIMIST MOON-SIGHTING: THE STUDY OF ISLAMIC CALENDAR DETERMINATION IN INDONESIA - Ahmad Adib Rofiuddin; Ahmad Izzuddin (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2022)
The Islamic calendar decision has always been a public discourse among Muslims at the beginning of Ramadan, Shawwal, and Dhulhijjah. It is often the case that different decisions made among Muslim groups in determining the first of Ramadhan, Syawal, and Dhulhijjah which will affect the public holiday in Muslim majority countries. This study incorporates the theory of limit proposed by Muhammad Syahrour to analyze the ongoing contestation of Islamic calendar determination. Based on the in-depth analysis, this study suggests that the height criteria of the crescent can be categorized as optimistic and pessimistic criteria. Crescent's altitude of 3 degrees is the lower limit of optimism in crescent observations. Pessimism can be seen from astronomical calculations in which hilal altitude is below 3 degrees. These two criteria could be supported by the existing scientific proof through the image of the hilal altitude below 3 degrees.